UNDERSTANDING SLL/US$ EXCHANGE RATE EXPECTATIONS IN SIERRA LEONE USING BOX-JENKINS ARIMA APPROACH - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields, 2020)
This study was carried out with the purpose of producing twelve out-of-sample forecast for a univariate Exchange Rate variable as a way of addressing challenges faced around dollarization issues in the Sierra Leone economy. In pursuit of this, the ARIMA model was utilized, with the best model [1,4,7] indicating that the Sierra Leone - Leone [SLL] currency will continue to depreciate against the United States Dollar [US$] throughout the year 2020. This was done on the assumption of Ceteris Paribus condition, and most importantly on the view that past events of the univariate exchange rate variable are a determinant of future outcomes or performances. Robustness check was also carried out on within-sample forecast; the within-sample forecast was also utilized to produce out-of-sample forecast for a twelve months duration and this was then compared with the original out-of-sample result. Overall, results from the robustness results proved consistent with each other and only with infinitesimal level of error. In a bid to moving forward, recommendation for policy actions were highlighted, particularly in relation to the establishment of collaboration between relevant policy institutions like the Bank of Sierra Leone and the Ministry of Finance to address issues of concern, for example, a boost to the real sector and many more - in view of the current crisis of COVID-19, action of the central bank seem to be well in place to address abuse of the exchange rate system by unscrupulous traders / importers).